(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
Iron deficiency anemia is considered as one of the major public health problem in Bangladesh. Cardiac autonomic nerve dysfunction may present in iron deficiency anemia which increases the risk and further complications of this disease. Assessment of heart rate variability (HRV) is a non-invasive technique to evaluate cardiac autonomic nerve function status. To assess the cardiac autonomic nerve function status by heart rate variability analysis in female with iron deficiency anemia. This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2012 to June 2013. For this, 100 female subjects with iron deficiency anemia aged 20-45 years were included in the study group (Group B). The anemic subjects were selected from Outpatient Department of Haematology in Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. They were included in the study group on the basis of their pre-performed hemoglobin percentage, total count of RBC and serum ferritin level. Data were collected in pre-designed structured questionnaire by the researcher herself. For comparison, age and sex matched 100 apparently healthy female were selected as control (Group A) by personal contact from the different areas of Dhaka city. Analysis of HRV parameters were done in Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. The HRV parameters were recorded by a 4 active channels, Polyrite-D.For statistical analyses, unpaired Students t-test and Pearsons correlation coefficient test were performed by using SPSS (version-19) as applicable. Mean resting pulse rate and mean heart rate were significantly (p <0.0001) higher in subjects with iron deficiency anemia in comparison to those of control group. Hemoglobin concentration, total count of RBC, mean R-R interval, SDNN and RMSSD were significantly (p <0.0001) lower in subjects with iron deficiency anemia in comparison to those of healthy control. This study concludes that cardiac parasympathetic activity was reduced in female with iron deficiency anemia. DOI: http://dx.doi.org/10.3329/bjpp.v30i1.20779 Bangladesh J Physiol Pharmacol 2014; 30(1):1-5